2014
DOI: 10.1001/jamaoto.2014.75
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Sensorineural Hearing Loss Associated With Iron-Deficiency Anemia

Abstract: IMPORTANCE Vascular events play a big part in the development of sudden sensorineural hearing loss (SSNHL), but only those associated with sickle-cell anemia have been previously associated with SSNHL. This study demonstrates an association between SSNHL and prior iron-deficiency anemia (IDA).OBJECTIVE To evaluate the association between IDA and SSNHL using a nationwide population-based database.DESIGN, SETTING, AND PARTICIPANTS In this case-control study in Taiwan, participants with SSNHL (n = 4004) were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 44 publications
(23 reference statements)
0
34
1
1
Order By: Relevance
“…Numerous etiologies, including infection, otologic disease, and trauma, have been confirmed but most cases are idiopathic [2]. SSNHL may be associated with a variety of underlying comorbidities such as iron deficiency anemia, chronic kidney disease, systemic lupus erythematosus, diabetes mellitus (DM), human immunodeficiency virus, psoriasis, osteoporosis, and chronic otitis media (COM) [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous etiologies, including infection, otologic disease, and trauma, have been confirmed but most cases are idiopathic [2]. SSNHL may be associated with a variety of underlying comorbidities such as iron deficiency anemia, chronic kidney disease, systemic lupus erythematosus, diabetes mellitus (DM), human immunodeficiency virus, psoriasis, osteoporosis, and chronic otitis media (COM) [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The etiology is unknown, but a recent study by Chung et al found a significant association between iron deficiency anemia (IDA) and sudden SNHL [OR: 1.34 (95% CI: 1.11–1.61), p<0.01], which was most prominent in patients under 60 years-old. 5 IDA is a subset of anemia in which patients exhibit low hemoglobin, serum ferritin, serum iron, and increased soluble transferrin receptor. In United States adults, IDA is usually a result of blood loss, and usually responds well to reversal of the source of blood loss and oral iron supplementation.…”
mentioning
confidence: 99%
“…There are a few postulated pathophysiologies for SSNHL: (1) labyrinthine viral infection -there is a moderate prevalence of recent viral-type illness in SSNHL patients; about 17-33% of SSNHL patients recall a recent viral illness; however, 25% of patients without hearing loss visiting an otolaryngology clinic had experienced a virallike illness within a month [Okamoto et al, 1994]; (2) labyrinthine vascular compromise -the cochlea is an end organ with no collateral vasculature; thrombosis, embolus, vasospasm, or any pathology that results in reduced blood flow to the cochlea is a possible etiology for idiopathic SSNHL [Rudack et al, 2006]; (3) intracochlear membrane ruptures -rupture of either the membranes that separate the inner ear from the middle ear, or the delicate membranes within the cochlea that separate the perilymphatic and endolymphatic spaces could result in SSNHL, by creating a state of relative endolymphatic hydrops or altering the endocochlear potential, respectively [Chung et al, 2014;Goodhill et al, 1973;Simmons, 1968]; (4) immunemediated inner ear disease -the occurrence of SSNHL in autoimmune diseases, such as Cogan syndrome and systemic lupus erythematosus, is well documented, and (5) iron deficiency anemia [Chung et al, 2014]. Iron, in addition to zinc and copper, is essential to break down the free radicals for the enzymatic antioxidants.…”
Section: Discussionmentioning
confidence: 99%